Deep traps localization in AlGaN/GaN MIS-HEMTs by a comparative study using capacitance and current deep level transient spectroscopies. (May 2019) - El-Khatib, Mariam; Ferrandis, Philippe; Morvan, Erwan; Guillot, Gérard; Bremond, Georges
Abstract: In this study, deep traps in multiple-finger normally-off AlGaN/GaN metal-insulator-semiconductor high-electron mobility transistors (MIS-HEMTs) were identified. The localization of these traps has been established by a comparative study using capacitance and current deep level transient spectroscopies (DLTS). The Cgd -DLTS measurements cover the GaN buffer region between the gate and drain contacts. On the other hand, the IDS -DLTS measurements cover the channel region in GaN including the zone under the gate. Two electron traps, E2 (0.31eV) and E4 (0.5eV) have been detected. They are respectively attributed to reactive ion etching (RIE) induced surface damage. These two traps are more likely located in the GaN channel close to the gate. Two other deep electron traps E5 (0.64eV) and E6 (0.79eV) have also been detected and are localized in the GaN buffer layer.